Daily evolution of the balance of radiation components in a vineyard canopy at the Dão wine region, Portugal - Rodrigues, P. (2011)
In order to validate a model of vine transpiration based on radiative surface temperature a field trial was conducted in a vineyard in the Do region, centre of Portugal, with the cultivar "Touriga Nacional". The model is based on the partition of net radiation between the components of the canopy (vines, soil, and grass cover), considering that the vines and the undercover (sou plus grass cover) act separately and in parallel. Thus, the latent heat flux from the vines to the amosphere (XT) is determined from vine net radiation (Rn) and sensible heat flux (H). The partition of net radiation (Rn) between the undercover (Rn) and the vines (Rn) is made considering the exponential form for radiation extinction, with the coefficient of extinction being corrected with a factor dependent on the zenital solar angle (p) while leaf area index (LAI) is corrected with a clumping factor, Q(p). Sensible heat flux from the vines (H) is calculated from radiative temperature (Te) considering that the fluxes from the different origins are independent and that there are two resistances in series between the canopy and the atmosphere: the leaf boundary layer resistance (raHc) and the aerodynamic resistance of the crop (raH). Besides the estimation of the daily values of transpiration, the model allows to study the evolution of the different components of the radiation balance throughout the day. The daily evolution of the evaporation fraction from the vines (FE) can be approximated by a concave curve. Values of FE > 1 show that, under certain circumstances and periods of the day, energy used for transpiration (XT) is greater than crop net radiation, which indicates that there are exchanges of energy between the several components of the surface, namely when evaporative demand from the atmosphere is high and there are no soil water restrictions. The model also shows that, regardless ofthe soil water status, transpiration is a big part ofRn when these values are low (in the beginning ofthe morning and late afternoon).